Serum Ferritin Status in Microcytic Hypochromic Anaemic Medical Students (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Microcytic hypochromic anaemia is common in young adults , specially in females. It is important to know the serum ferritin status of the medical students who will be involved, in future, with the health care delivery system and to prevent anaemia among them. Objective: To observe the serum ferritin status in microcytic hypochromic anaemic medical students. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2009 to June 2010. A total number of 516 apparently healthy young adults of both sexes, age ranged from 18 to 22 years , were selected for the study from two medical college in Dhaka city. Of them, 276 were nonanaemic (control group A) and 240 were anaemic (study group B). Again , anaemic (B) subjects are divided into anaemic female (B1) and anaemic male (B2) . Among the anaemic (B) subjects, 170 had normocytic normochromic , 68 had microcytic hypochromic and 2 had macrocytic hypochromic anaemia. Serum ferritin was estimated by Micro-particle Enzyme Immunoassay in subjects (68 in number) who were suffering from microcytic hypochromic anaemia. The statistical analysis was done by using unpaired t test , Pearsons correlation coefficient test as applicable. Result: The mean serum ferritin level was almost similar and showed no statistically significant difference between group B1 and B2. Again, a significant positive correlation of serum ferritin level with haemoglobin was observed in both female and male in microcytic hypochromic anaemic group. Conclusion: This study reveals that serum ferritin level is one of the most sensitive and accurate indicator indicating iron status and thus microcytic hypochrmic anaemia. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20077 Bangladesh J Physiol Pharmacol 2012; 28(1&2):23-28